Interactive-Animative Learning Videos as an Instructional Medium for Social Studies Learning for Elementary School During the Covid 19 Pandemic - Adi Prehanto; Nuraly Masum Aprily; Anggit Merliana; Manjilati Nurhazah (Indonesian Journal of Primary Education, 2021)
The pandemic of Covid 19 requires teachers to guide their students through distance or online learning. Effective learning should always be explored so that students' learning outcomes does not decrease during this pandemic. It is certainly not easy to carry out effective and fun learning for students. Teachers keep always try the latest ideas every single time. Interactive video is one of the most appropriate strategies to solve learning problems in the classroom. This study aims to find out: 1) the percentage of students who responds positively to animative-interactive learning videos; 2) the percentage of students who does not respond to animative-interactive learning videos; 3) the percentage of students who responds negatively to interactive learning videos. This data was gained from 104 students of elementary school throughout in District of Tasikmalaya and Majalengka who learned Social Studies. Overall results analyzed through percentage form based on the students' response qualifications. The study was conducted by three observers who researched in different primary schools. Through this research, it was obtained that the use of Animative-interactive learning videos was effectively implemented as a learning strategy during this pandemic covid 19. The use of this media was also appropriate to be applied in the subjects of primary school of class of VI, because it was able to increase interest and explore the creativity of students. Through suitable analysis of the characteristics of learners, this type of media would be a reference for teachers to the implementation of learning that should use learning media that was fun and liked by students.